Image, Time, and Photography Based on Heidegger’s Kant and the Problem of Metaphysics - Farideh afarin; Sam Ghazanfari (Journal of Philosophical Investigations, 2023)
In Kant and the Problem of Metaphysics (KPM), Heidegger shows how the initial image-making power of the imagination is pictorial in the pure image of time. He further clarifies the recognized link between the syntheses and the time-visualizing power of images which is pictorial formative power, which can visualize time. The three syntheses of imagination are replaced with the modes of existence of Dasein. Three kinds of photographs resemble the images produced when the transcendental imagination functions as Dasein. We can address the ways to visualize time by considering Dasein with a photographic preoccupation through 1. A possible look in the form of presentation (a photograph shows an immediate look of a house or person as intuitable this-here); 2. An immediate look of the thing, house, or deceased person, as well as a copy or its reproduction as a death mask; and, 3. The manner of contemplation of a likeness is an immediate look of a being present in the form of representation.